Structural and Optical properties of Multiwalled Carbon Nanotubes Modified by DBD Plasma at Atmospheric Pressure - Norain Sahari; Zolkafle Buntat; Zulkifli Azman; Zainuddin Nawawi; Muhammad Abu Bakar Sidik; Muhammad Irfan Jambak (Universitas Ahmad Dahlan, 2018)
Structure, chemical, and physical properties of Multiwalled Carbon Nanotubes (MWCNTs) after modification by dielectric barrier discharge (DBD) at atmospheric pressure is investigated using Transmission Electron Microscopy (TEM), Raman and Uv-vis-NIR spectroscopy. Effects of plasma treatment time on MWCNTs are analyzed. TEM result shows that during the short period of plasma treatment time of 5 minutes, the tube surface experienced a few damages. With increase in plasma treatment time, the tube surface is damaged to a certain extent. Intensity ratio, ID/IG through Raman analysis shows a good agreement with TEM. The values of ID/IG of the modified MWCNTs are larger than those of pristine MWCNTs. An increase of ID/IG indicates that considerable defects are produced on the surfaces of MWCNTs. The treated MWCNTs has energy band gap compared to zero band gap of untreated MWCNTs. It is believed that the defect site of MWCNTs can modify the electronics properties of MWCNTs from being metallic to semiconducting structure, which is applicable for almost all electronics device applications.